Determinants of working capital requirement in listed firms: Empirical evidence using a dynamic system GMM - Joseph Dery Nyeadi; Yakubu Awudu Sare; Godfred Aawaar (Cogent Economics & Finance, 2018)
Working capital management is a critical element in the survival of every firm. While the effective management of working capital leads to value creation in firms, ineffective management of working capital, on the other hand, does not only destroy value but can lead to the eventual solvency of the firm. The search for the factors that influence working capital management has, therefore, become a worthwhile exercise embarked upon by both managers and scholars. The main aim of this study is thus to empirically investigate the determinants of working capital requirement on the listed firms in Ghana. In examining the determinants of working capital requirements, 28 firms listed on the Ghana Stock Exchange were used for a time period of 8 years, spanning from 2007 to 2014. The study employed a dynamic panel system of General Methods of Moments (GMM) to test the hypotheses. This estimator has the ability to produce consistent and unbiased results when even there is an endogeneity in the model. This, therefore, makes our results more efficient and reliable. First, the study suggests that working capital in Ghanaian firms is determined by profitability, age, sales growth, GDP growth, operating cycles and leverage. Second, it is realized that while age, profitability and operating cycle strongly impacts positively on working capital, GDP growth, sales growth and leverage inversely correlate with working capital.
Keywords: 330; working capital requirement; GMM; operating cycle; and Ghana